Using measurements of soil probes to help landscape management in different Hungarian regions - Dobó, Zsófia; Oláh, Izabella; Farkas, Róbert (JOURNAL OF LANDSCAPE ECOLOGY, 2017)
Our climate is continuously warming, and it has effect on soils as well. The soil temperature and buffer capacity of soil against atmosphere temperature influence the range of crops to be grown on arable land. The aim of our search is to analyses soil temperature data measured by newly developed soil probes on a Gödöllő sample area, Hungary. Soil probes measure temperature at different depths, in 15 minutes intervals. At 8 cm depth the daily fluctuation is more than 30°C, while it decreases to a 10°C on average at 80 cm depth. Statistically soil temperatures differ between in different depths, so the temperature change is obvious. We investigate data measured at the same depth, which enables us to describe the heterogeneity of the sample field. It is clear that there are differences between parts of sample field, even at the same depths. Our long-term goals include facilitating landscape management, drawing conclusions on not just at a field scale but at regional levels. To reach this goal, the analyses of one field is not enough, more fields need to be investigated.
Keywords: soil probe; soil temperature; temperature dynamics